Allelic variation and prevalence of serum opacity factor among the Streptococcus suis population - Daisuke Takamatsu (2018)
Serum opacity factor of Streptococcus suis (OFS) has recently been identified as a virulence determinant of an S. suis strain. In this study, we investigated the prevalence and variations of the ofs gene among 108 S. suis isolates from diseased and healthy pigs, and human patients. PCR screening and sequencing analysis showed that besides the ofs gene reported already (designated type 1 ), there were three allelic variants of ofs (designated types 2 to 4). Type-1 and type-2 ofs genes were expected to encode functional OFS, and SDS extracts of the isolates with type-1 ofs and type-2 ofs opacified horse serum. Culture supernatants of the isolates with type-2 ofs also showed strong serum opacification activity. In contrast, type-3 ofs was interrupted by a point mutation and type-4 ofs was disrupted by either insertion of an IS element or genetic rearrangement, and therefore the SDS extracts and culture supernatants of the isolates with type-3 ofs and type-4 ofs did not show serum opacification activity. Regardless of their origins, approximately 30 % of the isolates possessed functional OFSs, although type-2 ofs was found only in three isolates from healthy pigs. Multilocus sequence typing analysis showed that most of the isolates with type-1 ofs belonged to the sequence type (ST)1 complex, and most of the isolates with type-3 ofs and type-4 ofs belonged to the ST27 complex. The isolates with type-2 ofs were not assigned to a major ST complex. These results suggest that type-1 OFS contributes to the virulence of a limited number of S. suis isolates, i.e. those of the ST1 complex type, whereas other S. suis may not possess this category of virulence factor; the importance of type-2 OFS is obscure. © 2008 SGM.